STRATEGIES IN THE TRANSLATION OF REFUSAL EXPESSIONS IN JOHN GREEN’S PAPER TOWNS - Umi Nur Lailah; Susie Chrismalia Garnida (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2018)
This article examined about translation from English to Indonesian related to non-equivalence words on expression ofÂ refusalÂ either directly or indirectly, and the using of translation strategies in adjusting non-equivalence. This study focused to expression of refusal either directly or indirectly in English on Paper Towns novel by John Green (2008) as a source of data. There are 33 total data, consists of 22 of expression of indirect refusal and 11 expression of direct refusal. Those data are analysed by descriptive qualitative method. The result shows that strategy used for solving non equivalence problem in this translation are seven (7): (1) translation by more general word, (2) translation by more neutral word, (3) translation by cultural substitution, (4) translation using a loan word, (5) translation by paraphrasing using a related word, (6) translation by paraphrasing using an unrelated word, and (7) translation by omission. From all those strategies, strategies five (5) is often used in the translation because there is no suitable expression in Indonesian from English.